ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI KERJA PENDUDUK LANJUT USIA DI KABUPATEN TABANAN - Laksmi, Ni Luh Putu Pitaloka; Yasa, I Gusti Wayan Murjana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 10 No 10 (2021): VOL 10 NO 10, OKTOBER 2021 [3966 - 4405], 2021)
The increase in life expectancy indirectly causes an increase in number of elderly people. The phenomenon of population aged 60 years and over who can be categorized as elderlypeople still working is stillfound in Bali,  especially in Tabanan Regency. The results obtained stated that 1) age, education, family income, and number of dependents simultaneously had a significant effect on the work participation of the elderly population in Tabanan Regency. 2) age, education, and family income partially have a negative effect, while the number of dependents has a positiveeffect on the work participation of the elderly population in Tabanan Regency. 3) The number of dependents as a moderating variable strengthens the effect of family income on the level of work participation of elderly residents in Tabanan Regency.